Phenomenological Study on the Meditation Experience of Qigong Practitioners - Kim, Mi-Na; Lee, Myung-Sun (Cuestiones de Fisioterapia, 2024)
This study conducted in-depth, one-on-one interviews with three long-term Qigong practitioners who have been consistently practicing meditation for over 20 years to analyze the significance of their meditation experiences and the changes these practices have brought to their lives through phenomenological research. The findings reveal that, through the course of over two decades of meditation practice, these long-term Qigong practitioners have experienced natural healing, are now able to regulate their bodies to maintain health, manage stress through mind control leading to comfort, deep sleep, and smoother interpersonal relationships. They reported an increase in life's wisdom, abundance, joy, happiness, gratitude, consideration, compassion, and altruism, resulting in a more relaxed life. Furthermore, by recognizing the true self, comprehending situations, and gaining awareness, they have engaged in self-reflection and internal growth, leading to positive changes in their life values and an overall improvement in the quality of life.The study suggests that for future research to achieve a deeper and more scientific understanding of meditation, experiential research that involves researchers directly experiencing and observing the profound states of meditation is also necessary.